Arsenic sulfide reverses cisplatin resistance in non‐small cell lung cancer in vitro and in vivo through targeting PD‐L1. Issue 19 (1st September 2021) - Tian, Wei; Sun, Yinping; Cheng, Yuping; Ma, Xiao; Du, Weina; Shi, Wenna; Guo, Qisen
Abstract: Background: Recent studies have found that programmed death ligand 1 (PD‐L1) might be involved in chemotherapy resistance in non‐small cell lung cancer (NSCLC). Arsenic sulfide (As4 S4 ) has been recognized to have antitumor activities and enhance the cytotoxic effect of chemotherapy drugs. In this study, we aimed to verify the relationship between PD‐L1 and cisplatin (DDP) resistance and identify whether As4 S4 could reverse DDP resistance through targeting PD‐L1 in NSCLC. Methods: The effect of As4 S4 and DDP on cell proliferation and apoptosis was investigated in NSCLC cell lines. The expression of p53 and PD‐L1 proteins was measured by western blotting analysis. The levels of miR‐34a‐5p, miR‐34a‐3p and PD‐L1 in cells were measured by real‐time qPCR analysis. Mouse xenograft models were established by inoculation with A549/DDP (DDP‐resistant) cells. Results: Depletion of PD‐L1 inhibited DDP resistance in A549/DDP and H1299/DDP cells. As4 S4 was capable of sensitizing A549/DDP cells to DDP by enhancing apoptosis. As4 S4 upregulated p53 expression and downregulated PD‐L1 expression in A549/DDP cells. As4 S4 increased miR‐34a‐5p level in A549/DDP cells. Inhibition of p53 by PFT‐α partially restored the levels of PD‐L1 and miR‐34a‐5p. Pretreatment with PFT‐α suppressed the apoptosis rate induced by cotreatment of As4 S4 and DDP in A549/DDP cells. Cotreatment of DDP and As4 S4 notably reduced the tumor size when compared with DDP treatment alone in vivo. Conclusions: Upregulation of PD‐L1 was correlated with DDP resistance in NSCLC cells. Mechanistic analyses indicated that As4 S4 might sensitize NSCLC cells to DDP through targeting p53/miR‐34a‐5p/PD‐L1 axis. Abstract : PD‐L1 is correlated with DDP resistance in non‐small cell lung cancer. As4 S4 reverses DDP resistance through targeting PD‐L1 in NSCLC in vitro and in vivo.